O gênero multimodal tiras sob a perspectiva dos multiletramentos: uma proposta de sequência didática para o 9º ano do ensino fundamental II - Angelo , Monique Viana de Oliveira (2021)
This work postulates as general objective to present a didactic sequence based on the research of Lopes-Rossi (2011), involving the multimodal genre strips from the perspective of multiliteracies. This sequence is aimed at 9th grade classes of elementary school at a municipal public school in the city of Araçagi / PB. In this perspective the main theoretical basis for our proposal uses the theories and researches of Kleiman (2010), Rojo (2013), Street (1984; 2007), on the aspects of literacies and multiliteracies, Bakhtin (1997) and Marcuschi (2008) in the rationale of the genre, Dioníso (2006), Kress & Van Leeuwen (2006) about multimodality, as well as Ramos (2017) and Rama; Vergueiro (2009), about the genre strips, in consonance with the official documents PCN (1998) and BNCC (2018). To this, we will develop a didactic sequence, taking Lopes-Rossi's (2011) conceptions as a parameter. Considering the contemporary scenario marked by the multimodality of the texts and the different languages, working with strips is justified, as they, in addition to being valuable educational tools attractive to students, are rich in resources that allow different readings in the promotion of multiliteracies. Therefore, we hope that the work with reading / writing through the strips, makes our proposal viable promoting the critical formation of the subjects involved in a hypermodern scenario.